Determination of the relationship between percentage of hypo-osmotic swelling test scores and antisperm antibody assay in infertile patients after IUI technique - KH.Kouti, Bassim; M.Fakur Al deen, Mohammed – Baqer (University of Thi-Qar Journal of Science, 2019)
This study was devised to compare the results of hypo-osmotic swelling (HOS) test and antisperm antibody assay (ASA) for normozoospermic men and infertile patients affected by autoimmune infertility. Thirty semen samples were collected by masturbation and prepared by direct layering technique for IUI procedure. Hypo-osmotic swelling test was performed by mixing 0.1 ml of semen with 1.0 ml of a 150 mOsm/ L NaCl as a hypo-osmotic solution and direct immunobead assay were used to determine the presence of ASA bound on the sperm surface. However, sperm concentration, sperm motility, progressive sperm motility, normal sperm morphology were evaluated according to standard World Health Organization (WHO) criteria and subjected to HOS test and ASA assay. The sperm prepared and incubated for 30 minute in 5% COat 37ºC after in vitro sperm preparation. The results reported that the percentage of HOS test score in ASA positive (55.20 ± 7.1) sperm samples was significantly lower than that noticed in ASA negative (73.32 ± 4.8) sperm samples (P<000.1). As a result, eight clinical pregnancy rates were accounts for normozoospermic men without ASA and normal HOS test after in vitro sperm activation and IUI procedure. Therefore, it was concluded that the use of HOS test as a simple and dependable test to identify successful pregnancy after intra-uterine insemination. Further studies are suggested to assess the effect of ASA on sperm plasma functional integrity after ICSI and IVF-ET.